Global status and future prospects of research in cotton leaf curl disease. (9th May 2018) - Naveed, Khalid; Abbas, Amjad; Khan, Sajid Aleem; Amrao, Luqman; Ali, Muhammad Amjad
Abstract: Begomoviruses are economically important plant viruses with a wide host range infecting numerous vegetables, legumes and fibre crops worldwide. Pakistan cotton suffered with cotton leaf curl disease (CLCuD) epidemic in the 1990s resulting in huge crop losses. Since then CLCuD has become a continuous threat to cotton industry in Pakistan. Several monopartite begomovirus species and satellite molecules are associated with CLCuD. There is threat of disease spreading to other parts of the world which are currently free from CLCuD due to agricultural trade and spread of vector, Bemisia tabaci. Natural resistance in tetraploid cotton, Gossypium hirsutum against CLCuD is very limited and is not durable under field conditions due to emergence of new viral strains. Genetically engineered resistance towards CLCuD has had limited success due to transformation limitations in cotton and the diversity of begomoviruses. Molecular approaches and conventional breeding are underway for developing cotton with CLCuD resistance. There is need to introgress multiple resistance genes in cotton to produce durable resistance which would lost several years. The review is an update on the current status and future prospects of CLCuD.